THE RELATIONSHIP OF THE SOLUTION FOCUSED LEVELS OF MARRIED WOMEN ON THE GENITAL SELF IMAGES AND THE SPIRITUAL WELL-BEING - AYAR, Duygu; KARASU, Fatma; ÖZTÜRK ÇOPUR, Ebru (Göbeklitepe Medical Science Journal, 2021)
Aim: This study was conducted to determine the effect of the solution-focused levels of the married women on their genital self-image and spiritual well-being. Method: The cross-sectional study was conducted with 203 married-women who accepted the study between the dates of 09.15.2020-10.15.2020. The data of the study was collected through by using the Socio-demographic Question Form, the Solution-Focused Inventory, the Female Genital Self-Image, and the Spiritual Well-Being Scale. In the evaluation of the data, besides the descriptive statistics, t-test, ANOVA, and the correlation tests were used in the independent groups. The written consents of the both ethics committee and the participants were obtained to conduct the study. Result: The Solution Focused-Inventory’s total mean score of the married women was 60.59 ± 8.42; The Female Genital Self-Image Scale’s mean score was 20.07 ± 4.28; Total mean score of the Spiritual Well-Being Scale was determined as 118.18 ± 16.01. A weak and positive correlation was found between the Solution-Focused Inventory and the Female Genital Self-Image Scale (r = 0.298, p = 0.001) and the Spiritual Well-Being Scale (r = 0.381, p = 0.001). Conclusion: It was concluded that as the solution-focused levels of the married women increased, their genital self-image and the spiritual well-being also enhanced.